A Novel C-Type Lectin and Its Potential Role in Feeding and Feed Selection in Ruditapes philippinarum - Sentao Chen; Peng Shi; Qingkai Feng; Xiaoting Qiu; Jilin Xu; Xiaojun Yan; Chengxu Zhou (Fishes, 2023)
In recent years, the role of lectins in the feed selection of bivalve has become hot research topic. Manila clam Ruditapes philippinarum is a species of marine bivalve with important economic value. A new C-type lectin (Rpcl) from the clam was obtained and its potential role in feeding and feed selection was studied. Rpcl cDNA was 929 bp in length and had 720 bp of open reading frame. Rpcl encoded 235 amino acids, comprising a carbohydrate recognition domain (CRD) as well as an N-terminal signal peptide. Rpcl contained a conserved CRD disulfide bond including five cysteine residues (Cys125, Cys142, Cys213, Cys219, and Cys237) and the QPN motif (GLN204-PRO205-ASN206). Phylogenetic analysis revealed that the amino acid sequence of Rpcl was closely related to that of Vpclec-1 from R. philippinarum and C-type lectin from Mercenaria. The qPCR analysis indicated that Rpcl expression was observed in all examined tissues and was the highest in gills followed by in the hepatopancreas, and to a lesser extent in the mantle and lip. The in vitro agglutination experiments showed that, the purified Rpcl protein could selectively agglutinate with different microalgae. The strongest agglutinating effect with Chlorella sp. was observed, followed by Karlodinium veneficum and Chaetoceros debilis Cleve. No agglutination with Prorocentrum minimum was observed. In the feeding experiment, compared with that of the starvation group, Rpcl expression in the lip and gill of the clam fed with C. debilis and K. veneficum showed a significant upward trend with the change of time. In addition, it was found that the changes in the expression of the Rpcl gene in the gill and lip, the main feeding tissues, were consistent with the slope of the decrease in the number of algal cells in the water body. In summary, the structure of a new C-type lectin (Rpcl) was reported in this study and its correlation with the feeding and feed selection in R. philippinarum was confirmed.